The Legal Advantages Of Blockchain Technology For Notary Protocol Archives - Kridawidyani, Widya; Indradewi, Astrid Athina; Sugianto, Fajar; Michael, Tomy (Journal of Law and Policy Transformation, 2023)
This paper discusses the legal advantages of using blockchain technology for notary protocol archives in Indonesia. This research is normative legal research. It uses primary and secondary legal materials to analyze the blockchain technology for notary protocol archives. With the development of information technology, notary services are inevitably shifting to electronic services, known as cyber notaries. The Notary Protocol is considered a state document and must be treated as such, stored, and kept authentic according to Law of Republic of Indonesia Number 30 of 2004 concerning Notary. Even if the notary who owns the protocol is on leave or dies, the protocol is categorized as a State Archive and is subject to Law of Republic of Indonesia Number 43 of 2009 concerning Archives. Blockchain technology offers a decentralized way of digital archiving.